Properties and Biodegradability of Thermoplastic Starch Obtained from Granular Starches Grafted with Polycaprolactone - Z. B. Cuevas-Carballo; S. Duarte-Aranda; G. Canché-Escamilla (International Journal of Polymer Science)
Granular starches grafted with polycaprolactone (St-g-PCL) were obtained using N-methylimidazole (NMI) as a catalyst. The effect of the starch/monomer ratio and catalyst content was studied to obtain different levels of grafted PCL. The highest grafting percentage (76%) and addition (43%) were achieved for reactions with a starch/monomer ratio of 50/50 and 25% catalyst. The grafting of PCL on the starch granule was verified by the emergence of the carbonyl group in the FTIR spectra and the increased diameter of the grafted starch granule. Thermoplastic starch from ungrafted starch (TPS) and grafted starch (TPGS) was obtained by mixing ungrafted or grafted starch granules with water, glycerol, or sorbitol in a mixer. TPS and TPGS behave as plastic materials, and their mechanical properties depend on the type of plasticizer used. Materials with glycerol as the plasticizer exhibited less rigidity. The presence of starch-g-PCL results in a dramatic increase in the elongation of the thermoplastic material. The starch present in the TPS or TPGS was completely biodegraded while the grafted PCL was partially biodegraded after the enzymatic degradation of the materials.